2013
DOI: 10.1016/j.jcmg.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Reconstruction to Preserve Image Quality and Diagnostic Accuracy at Reduced Radiation Dose in Coronary CT Angiography

Abstract: Compared with a routine radiation dose FBP protocol, 50% reduced dose acquisition using IR preserves image quality and diagnostic accuracy at coronary CTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 25 publications
1
53
0
Order By: Relevance
“…The last 7 questions (No. [19][20][21][22][23][24][25] referred to the storage and interpretation of cardiac CT data sets (e.g., overall duration), and the future needs for cardiac CT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The last 7 questions (No. [19][20][21][22][23][24][25] referred to the storage and interpretation of cardiac CT data sets (e.g., overall duration), and the future needs for cardiac CT.…”
Section: Introductionmentioning
confidence: 99%
“…In the past eight years, dozens of effective strategies to reduce radiation dose have become available, even a submillisievert CCTA scan has become feasible [23][24][25][26] . In our survey, the median dose among hospitals was 10-15mSv, and the median dose among patients was 6-9mSv, which is demonstrating improvement as compared to 2007.…”
mentioning
confidence: 99%
“…24 In addition, iterative reconstruction algorithms are a post-processing option available for reducing radiation dose at CT. Several studies have shown that iterative reconstructions allowed a 50% reduction in dose deposition, while preserving image quality and diagnostic accuracy of coronary CTA. 7,25,26 Schuhbaeck et al demonstrated that for a coronary-CT, the addition of high-pitch with raw databased iterative reconstruction results in a furthermore decrease in dose, while providing sufficient image quality with an estimated effective dose <0.1 mSv. 27 In the present study, the acquisition protocol was optimized for CTA of the thoraco-abdominal aorta and not exclusively for the heart.…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of new generation dual-source CT, high-pitch CT and new iterative reconstructions have led to image improvement by decreasing movement artifacts, decreasing image noise and increasing CNR of vessels. 6,7 Published data addressing the ability of such protocols to allow accurate and combined explorations of both aortic and coronary arteries during the same acquisition are scarce, especially with low radiation deposition and regardless of the heart rate. The purpose of this study was to evaluate the image quality and CNR of uniquely thoraco-abdominal ECG-gated acquisition with a high-pitch and iterative reconstructions algorithm for the exploration of both the aorta and coronary arteries.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, data from the PROTECTION I study showed that the average radiation dose from conventional retrospective electrocardiogram-gated CCTA was 11.2 mSv. 25 More recently, high-pitch helical dual-source scanning, 26,27 automatic attenuation for radiation dose optimization, 28,29 and padding reduction 30,31 are emerging as innovative methods to reduce radiation exposure from MDCT.…”
Section: Advances In Radiation Exposure Reductionmentioning
confidence: 99%